Z dyskusji nad referendum w Polsce Ludowej - Krzywoszyński , Przemysław (Czasopismo Prawno-Historyczne, 2009)
In the period of the Polish People's Republic (1944 to 1989), there was a clear disproportion between the practice and the theory of a referendum. Although during the whole period direct elections were held only twice (1946 and 1987), discussions on the chances of holding a referendum had continued all the time. The first referendum that was held was so designed that it allowed the communists to take over power "lawfully." The other election, held shortly before the end of the Polish People's Republic rule, at the time when the political and economic crisis was accelerating, was less successful for the government in office, and failed to secure sufficient support to the leading party. The discussions on the political and legal issues that followed went far beyond the elections, though. Other important issues involved "people's" or "socialist" democracy.